JEJAK INTELEKTUAL ILMUWAN MUSLIM PADA MASA KEEMASAN ABBASIYAH - Rahmawati, Nadia; Sabariani, Ranti; Hudaidah; Yati, Risa Marta (BANDA HISTORIA: Jurnal Pendidikan Sejarah dan Studi Budaya, 2025)
The Abbasid Dynasty (750–1258 AD) marked the peak of Islamic civilization, characterized by extraordinary progress in science, philosophy, and culture. This study aims to describe the intellectual legacy of Muslim scholars during this golden era and analyze the factors that supported the advancement of knowledge, including political patronage, scientific institutions, and crosscultural collaboration. Using a historical-descriptive approach through literature review, this research explores the role of institutions such as Bayt al-Hikmah (House of Wisdom) as centers for translation, research, and innovation. The study finds that the combination of government support, inclusive social structure, and an open intellectual environment contributed to the flourishing of scientific disciplines such as mathematics, medicine, astronomy, chemistry, and philosophy. Prominent figures like Al-Khwarizmi, Ibn Sina, Jabir ibn Hayyan, and Al-Farabi not only preserved classical knowledge but also developed new ideas that influenced both the Islamic and Western worlds. The Abbasid intellectual heritage became the foundation for the Renaissance and the development of modern science.